Myoxanthus anancusiensis (Orchidaceae: Pleurothallidinae), a new species from the inter-Andean valley of Huancavelica, Peru - Cuadros-Rojas, Robinson Daniel; Quispe-Melgar, Harold Rusbelth; Calderon-Quispe, Fernando H.; Singer, Rodrigo B. (Phytotaxa, 2023)
We report a new species of Myoxanthus from Huancavelica, Peru. Myoxanthus anancusiensis is described, illustrated, and compared with its similar species M. serripetalus and M. oliviae. We carried out a systematic review of the herbarium information of Myoxanthus species reported for Peru and compared the morphological characteristics of similar species, to rule out overlooking already described taxa. The new species is characterized by being a medium-sized plant with a terrestrial habit that grows at an elevation of 2800 m. The flower is cherry-red in color with slightly yellow striations. The sepals present a smooth adaxial surface, and the petals are oblong-caudate with entire margin. The labellum is oblong-elliptic and fimbriate with lateral lobes erect. The new species represents an important record for the flora of the inter-Andean valleys of central Peru in the department of Huancavelica and suggests that carrying out more expeditions in this type of ecosystem is desirable.